Characteristics of visual functions and their correlation with OCT-angiography of the macula in patients with small choroidal melanoma - Е.Б. Мякошина; S.V. Saakyan (РМЖ "Клиническая офтальмология")
E.B. Myakoshina, S.V. Saakyan Helmholtz National Medical Research Center of Eye Diseases, Moscow, Russian Federation Background: choroidal melanoma is the most common malignancy in ophthalmological practice. However, it is difficult to diagnose its early stages, since patients report non-specific symptoms. A delay in malignant tumor diagnosis is associated with metastasis and fatal outcome. Optical coherence tomography angiography (OCT-A) enables to visualize the ocular fundus microcirculation and, as a result, to achieve an earlier diagnosis of choroidal melanoma. Aim: to describe characteristics of the visual functions and their correlation with ophthalmoscopy and OCT-A findings in patients with small choroidal melanoma. Patients and Methods: the study involved 46 (92 eyes) patients with small choroidal melanoma, 17–84 years old (mean 59.67±14.2). All patients were split into 3 groups based on the tumor size. Group 1 (n=17): a prominence is 1.3±0.3 mm and a basal diameter is 6.8±2.2 mm; group 2 (n=12): a prominence is 1.7±0.4 mm and a basal diameter is 8.3±2.01 mm; group 3 (n=17): a prominence is 2.4±0.74 mm and a basal diameter is 9.75±0.47 mm. The control group consisted of healthy paired-eyes (n=46). Visometry with the evaluation of the uncorrected and maximum-corrected distance visual acuity was performed in all patients. Results: a correlation was found between the decrease in the uncorrected and maximum-corrected distance visual acuity and the tumor size (р<005). According to the OCT-A results, an area and perimeter of the foveolar avascular zone expanded with an increase in tumor size (p<0.05). As shown, a decrease in density of the perfusion and vessels in the superficial and deep capillary plexuses in all quadrants of the perifoveolar zone was associated with the tumor growth (p <0.05). Conclusion: the characterization of visual functions and their correlation with ophthalmoscopy is important for identifying the first signs of choroidal melanoma development.The assessment of OCT-A findings is a unique diagnostic criterion enabling to detect the first signs of macular microvascular disorders accompanying the manifestation and growth of extramacular choroidal melanoma. A timely diagnosis of small choroidal melanoma offers the opportunities of adequate treatment and, ultimately, improves the vital prognosis for patients with malignant tumor. Keywords: visual functions, OCT-angiography, maculopathy, small choroidal melanoma. For citation: Myakoshina E.B., Saakyan S.V. Characteristics of visual functions and their correlation with OCT-angiography of the macula in patients with small choroidal melanoma. Russian Journal of Clinical Ophthalmology. 2022;22(4):216–223 (in Russ.). DOI: 10.32364/2311-7729-2022-22-4-216-223.